The Importance of Enhancing the Role of the Judicial Commission in Enforcing the Code of Ethics and Guidelines for Judicial Conduct - Sasmita, Sandra (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The Judicial Commission is a state institution responsible for upholding and enforcing the code of ethics and conduct for judges, as mandated by Law Number 18 of 2011, which amended Law Number 22 of 2004. The Judicial Commission plays a crucial role in safeguarding judicial integrity through oversight based on the Code of Ethics and Guidelines for Judges' Conduct, as outlined in the Joint Decree of the Chief Justice of the Supreme Court and the Chairperson of the KY, Number 047/KMA/SKB/IV/2009 in conjunction with 02/SKB/P.KY/IV/2009. Despite these efforts, instances of judicial misconduct remain prevalent, highlighting the necessity of strengthening the Judicial Commission’s role. This study aims to evaluate the effectiveness of the current measures and propose strategies to enhance the Judicial Commission’s authority in supervising judges. Employing a normative legal research methodology, the study examines relevant regulations and decisions pertaining to the Judicial Commission. The findings indicate a critical need to expand the Judicial Commission’s scope and role, including refining mechanisms for oversight and enforcement of the code of ethics, to mitigate judicial misconduct and prevent abuses of authority.